An efficient query indexing mechanism for filtering geo-textual data - Cui, Yan (2014)
In the information era, large amount of geo-tagged data has given rise to our ability to make more reasonable decisions. The geo-tagged data is usually associated with related text information. For example, tweets tagged with geo-locations on Tweeter, and restaurant reviews tagged with the restaurant locations on Yelp.